Almost the Same but Incomplete: Orientalism and Eastern Resistance in Ben Okri’s “Belonging” - Dewi, Marisa Santi; Konning, Juliana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The prevailing sentiment is that colonialism is a thing of the past. However, the Western portrayal of the East is one of the shackles that still holds postcolonial societies. A diverse number of Orientalist writings and language perpetuate a rigid image of the people of the East as primitive, prone to tradition, and uncivilized. Such a representation tends to be perceived as true if it is told repeatedly, consistently, and continuously. This research attempted to provide insight into how imperialism operates in current discourses, how colonial power structures persist, and how these structures can be deconstructed, by presenting a re-examination of the presence of Orientalism in Ben Okri's short story, “Belonging” (2009), not as a careless reiteration of Western dominance, but as a type of Eastern resistance. This critical exploration was based on Edward Said's Orientalism theory and Homi Bhabha's Stereotype and Mimicry theory, and employed descriptive qualitative and deconstructive reading methods to re-evaluate the use of Orientalist stereotypes in the short story. The findings showed that the Orientalist view and stereotypes are unstable, creating a space for Eastern resistance against Western colonial discourse. This article thus sheds light on how Western perspectives on Eastern societies are embedded in literary works and at the same time discloses a possibility of resistance against Western stereotypes.